(untitled) (Medicine Today, 2019)
Introduction: Every day, nurses experience a great deal of stress. They face problems at work, people relying on them for their care, and also tons of responsibilities piling up at home. Psychological stress is common in hospital ward and associated with depression. Only few studies are done concerning mental health of Nurses in Bangladesh. The study was carried out with a view to find out the prevalence of depression among nurses at Mental Hospital, Pabna, Bangladesh. Materials & Methods: A cross sectional, questionnaire-based survey was carried out among the 125 nurses of Mental Hospital, Pabna. The studywas conducted between January to February 2019. The depression levels were assessed using Zung depression scale. Nurses were asked to complete the questionnaire and then the depression levels calculated. Result: The overall prevalence of depression among the nurses was 4.13 percent. The prevalence of depression was 4.5 percent among female nurses versus 2.94 percent in male nurses. Conclusion: The prevalence of depression is seen especially innurses. So, attempts should be made to alleviate the stressors. Medicine Today 2019 Vol.31(2): 111-113